Rethinking embeddedness: a review and research agenda - Wigren-Kristoferson, Caroline; Brundin, Ethel; Hellerstedt, Karin; Stevenson, Anna; Aggestam, Maria (Entrepreneurship and regional development, 2022)
We conduct a comprehensive review of embeddedness in entrepreneurship research. Although the term "embeddedness" is frequently used in this field of study, less is known about the ways in which it is operationalized and applied. Using criterion sampling, we analyse 198 articles in order to investigate how embeddedness is conceptualized and what role it plays in the extant entrepreneurship literature. We categorize our findings based on different phases of the entrepreneurial process (early, mature and exit) and outline the dominant focus and the main conceptualization of embeddedness for each phase. We highlight important learnings for each of the three phases and identify potential areas for conceptual development. Across the phases, we find that embeddedness and context are often used interchangeably. We thus call for construct clarity in the field. In the existing literature, entrepreneurs are generally portrayed as reactive to embeddedness, resulting in a loss of entrepreneurial agency. To remedy this, we introduce the term agencement, which takes into account the relationship between the entrepreneurship and embeddedness. Further, entrepreneurs are found to be embedded in multiple contexts at the same time, and embeddedness can be understood at different levels and to different degrees. To address this complexity, it is relevant to focus on the embedding process itself, acknowledging that it takes place in social interactions including cultural, cognitive, and emotional aspects between contexts and across levels. While the extant literature supports the notion that embeddedness is important for understanding entrepreneurship and entrepreneurs, it does not necessarily support our understanding of how embeddedness takes form or why it takes certain forms. We therefore include a call for future research to turn to process and practice theories.